Analysis of Influence of Intrinsic Aspect, Demography Aspect and Service of Zakat Institution toward Zakat Payment to Zakat Institution - Ahmad Mifdlol Muthohar (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
This study aimed to determine the concept of the blessing of zakat and the muzaki’s perception about the blessings and to find internal factors that affected the muzaki in issuing zakat to zakat institutions. These factors were the service of zakat institutions, muzaki’s religiosity, feeling blessed, gender, education level, and occupation, whether all of which affected the propensity of their choice in issuing zakat to zakat institutions. Sampling used purposive random sampling. For data analysis tools, this study used multiple regression analysis with tobit models. The findings in this study showed that the feeling of blessing by issuing zakat and occupational factors did not significantly influence the preferences of muzaki to issue zakat to certain zakat institutions. For the service of zakat institution, gender, and education level, they significantly and positively affected the preferences to issue zakat to zakat institutions. The variable of muzaki’s religiosity negatively affected the trend in the choice of muzaki to issue zakat to zakat institutions significantly.